Participation and Functional Independence in Adults With Recessive Spastic Ataxia of Charlevoix-Saguenay. (September 2022) - Muslemani, Samar; Lessard, Isabelle; Lavoie, Caroline; Côté, Isabelle; Brais, Bernard; Mathieu, Jean; Gagnon, Cynthia
Background. Autosomal recessive spastic ataxia of Charlevoix-Saguenay (ARSACS) is a progressive disorder where upper and lower extremities motor performances may bring participation restriction.Purpose. To document participation in adults with ARSAC and explore associations with motor performances.Method. Twenty-eight participants took part in the study. Participation was assessed using the LIFE-H. Motor performance was assessed using several outcomes including the SARA, LEMOCOT, Berg Balance Scale, 10-Meter Walk Test, and Finger-to-nose Test.Findings. Participation was significantly lower in the wheelchair user subgroup. Also, for 29 activities out of 77, at least 15% of participants reported severely disrupted participation. Participation was correlated with upper and lower limbs coordination, walking ability, balance, disease severity, and fine dexterity (Spearman r  = .41–0.85, p  < .03).Implications. Results showed significant participation restrictions and suggest that interventions aiming to improve or compensate upper and lower limbs functions could help to decrease disease burden.